2022
DOI: 10.30564/agger.v4i3.4939
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Subsurface Lithology and Aquifer Parameters Using Vertical Electrical Sounding (VES) for Groundwater Development in Igbo-Imabana, Southern Nigeria

Abstract: Vertical Electrical Soundings (VES) using Schlumberger array was carried out at fifteen (15) different points to evaluate aquifer characteristics within Igbo-Imabana, Abi L.G.A of Cross River State. Resistivity meter and its accessories were used for data acquisition. The maximum current and potential electrode distance were 400 m and 20 m respectively. The field data were interpreted using Interpex software and three to five geo-electric layers encountered within the study area. The dominant curve type was H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The region is characterized by the presence of a physically regulated and depressed aquifer type. The regulation of shallow groundwater in the studied area is influenced by various factors, including fractures, geometry (dip), fracture diameter, interconnectivity, and the confined structure of the aquifer [24,25]. The results of the analysis of the data showed that there were impermeable layers in the area being studied.…”
Section: Resultsmentioning
confidence: 95%
“…The region is characterized by the presence of a physically regulated and depressed aquifer type. The regulation of shallow groundwater in the studied area is influenced by various factors, including fractures, geometry (dip), fracture diameter, interconnectivity, and the confined structure of the aquifer [24,25]. The results of the analysis of the data showed that there were impermeable layers in the area being studied.…”
Section: Resultsmentioning
confidence: 95%